Survival Analysis in Young–Age Breast Cancer and Related Clinicopathologic Factors at dr. Cipto Mangunkusumo General Hospital 2008–2015 - Yulian, Erwin D.; Salim, Adrian (The New Ropanasuri Journal of Surgery, 2018)
Introduction. Various cancer registrations and reports had confirmed the higher proportion of young women with breast cancer in Asian countries. This mandates special attention for clinician since this group of patients need different management approach, especially regarding the more aggressive biological behavior, worse prognosis and the escalating psychosocial burden that young women endure. We conducted a study to describe the clinicopathological characteristics of young–aged breast cancer in Indonesia and its relationship with overall survival. Method. This study is a survival analysis using samples all young–aged women with histologically–proven cancer diagnosis that underwent treatment (surgery and/or chemotherapy and/or irradiation and/or hormonal therapy) since January 2008 to August 2015. Data were collected from both medical records and interview. Data were analyzed using SPSS Results. Young–age women comprise 35% of total breast cancer patients, with most cases were in the locally advanced stage, histologic type NST, grade 2, no lymphovascular invasion, positive hormone receptors, negative HER2 status, high Ki–67 and Luminal B subtype. The 5–year overall survival rates were 64%; variables that showed statistically significant correlation was tumor size, nodal status, metastasis status and clinical stage. Histologic type NST, grade 2, positive lymphovascular invasion, high Ki–67 and positive HER2 were related to survival, but this correlation was not statistically significant. Conclusion. Overall 5–year survival rates of young–aged breast cancer at dr.Cipto Mangunkusumo General Hospital was 64%, much lower that reported figures from literatures and other countries’ reports. Clinical stage was the only variable with statistically significant correlation. Luminal B subtype was observed the most, but the worst survival was found in the HER2 subtype group.